2011
DOI: 10.1101/gr.119867.110
|View full text |Cite
|
Sign up to set email alerts
|

A DNA methylation fingerprint of 1628 human samples

Abstract: Most of the studies characterizing DNA methylation patterns have been restricted to particular genomic loci in a limited number of human samples and pathological conditions. Herein, we present a compromise between an extremely comprehensive study of a human sample population with an intermediate level of resolution of CpGs at the genomic level. We obtained a DNA methylation fingerprint of 1628 human samples in which we interrogated 1505 CpG sites. The DNA methylation patterns revealed show this epigenetic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
238
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 362 publications
(270 citation statements)
references
References 81 publications
(130 reference statements)
16
238
1
6
Order By: Relevance
“…They were detected as hypermethylated in 9, 9, 17 and 20 tumors, respectively. Notably, CSPG2/VCAN was identified by Fernandez et al 17 to be hypermethylated in CRC, and not in 29 other cancers analyzed in their study.…”
Section: Dna Methylation Profiles Of Crc Cases and Matched Controlsmentioning
confidence: 98%
“…They were detected as hypermethylated in 9, 9, 17 and 20 tumors, respectively. Notably, CSPG2/VCAN was identified by Fernandez et al 17 to be hypermethylated in CRC, and not in 29 other cancers analyzed in their study.…”
Section: Dna Methylation Profiles Of Crc Cases and Matched Controlsmentioning
confidence: 98%
“…It is important to link these observations with our findings that the PRC2 signature is associated with aDMRs hypermethylated with age. Increase in methylation has traditionally been viewed as leading to decrease in gene expression, 29,32 suggesting these biological processes being downregulated with age. Indeed, prenatal hypomethylation following increased hypermethylation with age has been observed in normal brain development, 19 further suggesting that genes enriched in "neurogenesis," "synaptic transmission" and other brain-related processes identified in our study as being regulated by the PRC2 signature also undergo repression with age through hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenomic marks are generally tissue-and cell-type specific, 23,29,30 suggesting that age-dependent epigenomic changes may also be cell-or tissue-specific. 31 However, several studies have shown that methylation changes can be defined independently of sex, tissue type, cellular composition, differentiation status, and array platform.…”
Section: Introductionmentioning
confidence: 99%
“…84 This alteration is largely dependent on the action of de novo DNMTs during early tumor progression. 85 De novo DNMTs were previously suggested to promote tumorigenesis. 86 Early studies reported that the DNMT3A overexpressed in multiple tumor types, [87][88][89][90] and a poorer recurrence-free survival was noted in HCC (Hepatic Cellular Cancer) patients with >4-fold increase in DNMT3A mRNA.…”
Section: The Dual Roles Of Dnmt3a In Cancermentioning
confidence: 99%